The Effects of TRX-Based Movement Pattern Correction Exercises on the Landing Biomechanics and Balance of Female Volleyball Players Susceptible to Knee Injuries - Mohammad Kalantariyan; Niloufar Rahmani; Hadi Samadi (Islamic Azad University, Hamedan Branch, 2023)
Objective Movement pattern correction exercises using TRX are a novel approach that has recently attracted the attention of researchers. Therefore, the purpose of this research is to investigate the effect of movement pattern correction exercises using TRX on the landing biomechanics and balance of female volleyball players prone to knee injuries. Methods Twenty female volleyball players prone to knee injuries were selected based on specific criteria and split into two groups: one practiced TRX-based movement correction exercises, while the other served as the control. Initial assessments included anthropometric measurements, static/dynamic balance, and landing biomechanics using various tests. The training group underwent exercises three times a week for six weeks, while the control refrained from impactful sports activities. All participants continued their volleyball routines. Post-training, the same assessments were conducted, and statistical analyses were performed using paired t-tests and analysis of covariance to evaluate the results. Results The paired t-test results showed that the static and dynamic balance and landing mechanics of the subjects in the experimental group improved significantly in the post-test stage compared to the pre-test (p < 0.05), while there was no significant difference in the investigated variables in the control group (p ≤ 0.05). Additionally, the results of the analysis of covariance showed a significant difference in the scores of the balance and landing error variables between the two groups in the post-test phase (p < 0.05).. Conclusion Improving balance and increasing a person's ability to control the movements of the trunk and knee joint during landing can probably occur due to the improvement in the performance of the core stabilizer muscles of the body. Therefore, the use of movement pattern correction exercises using TRX can be considered an effective approach to prevent knee injuries in susceptible female volleyball players.